Differential Regulation of DNA Methylation at the CRMP2 Promoter Region Between the Hippocampus and Prefrontal Cortex in a CUMS Depression Model - Xiang, Dan; Xiao, Jiawei; Sun, Siqi; Fu, Linyan; Yao, Lihua; Wang, Gaohua; Liu, Zhongchun (Frontiers in Psychiatry, 2020)
Abstract: Current evidence supports the idea that neural plasticity is a potential cause of depression. Abundant studies indicate that CRMP2 has important roles in neural plasticity. Moreover, CRMP2 may contribute to the etiology of depression. However, the regulatory mechanisms underlying the role of CRMP2 remain unclear. DNA methylation alteration is generally acknowledged to be involved in the development of depression. The aim of this study was to explore the relationship between the expression and DNA methylation of CRMP2 - in the hippocampus and prefrontal cortex of a rat depression model. Chronic unpredictable mild stress (CUMS) was used to establish a rat depression model, and body weight and behavioral tests were used to evaluate the effects of stress. Real-time PCR and Western blotting were used to test CRMP2 mRNA and protein expression, respectively, in the hippocampus and prefrontal cortex of rats. DNA methylation levels of the CRMP2 promoter were analyzed by bisulfite sequencing PCR (BSP). CUMS caused depressive-like behavior in rats, as evidenced by decreased body weight and sucrose preference rate; decreases in the total distance traveled, rearing frequency, velocity and duration in the center in the open field test (OFT); and prolonged immobility in the forced swimming test (FST) . CRMP2 mRNA and protein expression in the hippocampus and prefrontal cortex were significantly decreased in the CUMS group compared with the control group. The levels of CRMP2 promoter DNA methylation in the hippocampus of the CUMS group were significantly higher than those of the control group, while these changes were not observed in the prefrontal cortex of CUMS rats. Our data provide evidence that altered expression of CRMP2 in the hippocampus and prefrontal cortex is associated with the pathogenesis of depression. Moreover, the results also suggest regional differences in the regulation of DNA methylation in the CRMP2 promoter between the hippocampus and prefrontal cortex during the development of depression.